Importance and Techniques of Water Harvesting Systems - Ali Kaan Yetik; Burak Şen (Turkish Journal of Agriculture: Food Science and Technology)
Efficient use of water, one of the most critical life elements in the world, is becoming more and more important day by day. With the continuous increase in population and with climate change problems occur in terms of both consumption rate and usage patterns of water resources. It is becoming increasingly important to apply and research methods that can solve these problems all over the world. One of these solutions is the “Water Harvesting” method, which goes back many years. Water harvesting can be defined as the accumulation of runoff generated by precipitation to provide water for human, animal or crop use. While it is possible to see the use of the technique with roof and farm systems in micro-catchment dimension; wadi-bed and off-wadi (diversion) systems are used in macro-catchment dimension. In agricultural production, which uses a significant part of water resources, most of the rainwater falling into arid and semi-arid regions where production continues, goes away before could using efficiently by evaporation or flow. For this reason, the use of water resources becomes mandatory by using traditional irrigation methods in agricultural lands. With the water harvesting technique, after storing rain water, it can be held to be applied to crops. Hence the method since there will be no losses due to evaporation or flow, it will increase the total amount of irrigation water and reduce the pressure on water resources. Except for the protection of water resources, its role in preventing soil erosion is also seen as one of the main benefits of the method. In general, when the appropriate method is selected according to the appropriate geography, water harvesting has low inputs and is not difficult to apply. With a few exceptions, it does not require the use of pumps or energy input to deliver or deliver harvested water. In this study, information is given about the main elements, different usage areas and techniques of water harvesting.